Recent advances in inhibition of porcine reproductive and respiratory syndrome virus through targeting CD163 - Zhang, Xiaoxiao; Guo, Chunhe (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) has plagued the pig industry for more than 30 years and causes great economic losses. At present different commercial vaccines are available but limited tools. Until now at least six potential host factors are identified as the key receptors for PRRSV infection. Among them, CD163 molecule is the most important and critical in PRRSV life cycle responsible for mediating virus uncoating and genome release. It determines the susceptibility of target cells to the virus. Several PRRSV non-permissive cells (such as PK-15, 3D4/21 and BHK-21) are demonstrated to become completely susceptible to PRRSV infection in the presence of expression of porcine CD163 protein. Therefore, CD163 has become the target for the design of novel antiviral molecules disrupting the interaction between CD163 and viral glycoproteins, or the breeding of gene-modified animals against PRRSV infection. In this review, we comprehensively summarize the recent progress in inhibition of PRRSV replication via targeting CD163 receptor. In addition, whether there are other potential molecules interacting with CD163 in the process of uncoating of virus life cycle is also discussed.